Російська дезінформація і пропаганда в соціальних медіа: кейс Телеграму - Сіріньок-Долгарьова, Катерина Григорівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The paper explores the social medium Telegram as a platform of spreading and circulating of Russian disinformation and propaganda in the time of full-scale Russian aggression against Ukraine. The author discusses the pros and cons of Telegram popularity among internet users in Ukraine, Russia and temporarily occupied territories of Ukraine. The challenges and threats of using Telegram as a messaging application as well as a social medium are analyzed, cyber security recommendations are proposed.